"Feasibility study for a recreational Tourist Center" - Carvajal Endara, Elmer Arturo; Batallas González, Irma Daniela; Almeida Yépez, Sandra Estefanía; Calderón Aconda, Valeria Yomaira (SATHIRI, 2018)
The construction of the recreational complex is located in the Urcuquí Canton, Province of Imbabura, this undertaking contributes to the strengthening of tourism and economic of the country, providing a high quality service that guarantees the welfare and satisfaction of the tourist; The size of the probabilistic sample is established in 384 people of the provincial population; Descriptive methods, qualitative and quantitative establishes the techniques for surveying clients and interviewing local owners, in addition the method of observation establishes aspects of the behavior of the competition; The statistical analysis of EXCEL determines the projection of the demand, the linear equation,   the correlation and the multifactorial analysis; The market, technical and organizational studies combined with the results obtained from the financial study and economic evaluation such as the NPV, IRR, B/C, Balance Point and Recovery Period applied conclude to be positive, which guarantees the feasibility and profitability of the project.